CVD precursors for transition metal oxide nanostructures: molecular properties, surface behavior and temperature effects. Issue 2 (8th October 2013) - Tabacchi, Gloria; Fois, Ettore; Barreca, Davide; Gasparotto, Alberto
<x xml:space="preserve">Abstract</x> Integrated analyses on a series of β‐diketonate‐diamine transition metal complexes (M = Fe, Co, Cu, Zn) highlight the metal center influence on molecular physico‐chemical properties and provide understanding of the favorable behavior of these compounds as precursors in the chemical vapor deposition (CVD) growth of metal/metal oxide nanomaterials. The Zn complex, which shows the most symmetric coordination environment in the gas phase, is activated in contact with the heated CVD growth surface model. First‐principles simulations evidenced surface‐induced rolling motion of the Zn precursor in the 363–750 K range, suggesting the relevance of vibrationally excited molecular rolling as activation pathway in high temperature surface chemistry. Molecular properties (left) and hot‐surface behavior (right) of the Zn(hfa)2TMEDA CVD precursor. <inline-graphic xlink:href="ark:/27927/pgg4swd4t6w" content-type="pssa201330085-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />